Strategi Peningkatan Jumlah Mahasiswa Program Studi Manajemen Zakat dan Wakaf - Sarmiana Batubara; Damri Batubara (ITB AAS INDONESIA, 2023)
Study programs have an important role in the development of an educational institution or college. Zakat and Waqf Management Study Program IAIN Padangsidimpuan is the only study program with a scientific field of zakat and waqf management in North Sumatra. However, student interest in choosing this study program is minimal and decreases every year. Meanwhile, the Zakat and Waqf Management Study Program at the State Islamic University of Raden Fatah Palembang has many students and continues to increase every year, so there is a significant difference in the number of students between the two study programs. the. The purpose of this study was to analyze the strategy of increasing the number of students in the Zakat and Waqf Management Study Program at IAIN Padangsidimpuan and UIN Raden Fatah Palembang in a comparative manner. This research is a qualitative research with comparative descriptive method. The results showed that the strategy carried out by the Zakat and Waqf Management Study Program at UIN Raden Fatah Palembang was maximal so that there was a significant increase in the number of students.